Integrated Management of Metropolitan Areas in Romania - Danielewicz, Justyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2020)
The rapid urbanisation of the world leads, among others, to dynamic development of metropolitan areas. The functional relationships between territorial units which make up a metropolitan area mean that the preparation of economically, spatially and environmentally coherent strategies needs to be coordinated at the metropolitan level in order to prevent negative effects of metropolisation and to ensure sustainable development of such an area. This in turn requires that the approach towards managing development shifts in favour of governance and integrated strategies. The paper aims at assessing whether the integrated planning and management is used in metropolitan areas in Romania. The desk research method was applied to analyse Romanian legislation for metropolitan areas, integrated strategies for the development of metropolitan areas and reports on their implementation. Interviews with representatives of selected associations of metropolitan areas provided additional valuable insight.